Changes in fatty acid profile and chemical composition of meagre (Argyrosomus regius) fed with different lipid and selenium levels. Issue 6 (14th December 2016) - Simões, Tiago; Fonseca, Sthelio B.; Augusto, Ana; Granada, Luana; Ozório, Rodrigo O.A.; Gonçalves, José F.M.; Pascoal, Leonardo A.F.; Silva, José H.V.; Lemos, Marco F.L.
Abstract : This study aimed to evaluate changes in body composition, specially muscle and liver fatty acid profile in meagre ( Argyrosomus regius ) fed with different dietary lipid sources and levels, with or without selenium supplementation. Six hundred meagre were fed twice a day, 6 days per week, with eight experimental diets for 60 days. Diets were a combination of fish oil or a vegetable blend (45% linseed + 35% rapeseed + 20% soybean oil), at 12 or 17% of oil and 0 or 1 mg/kg of organic selenium, in a 2 × 2 × 2 factorial design. The whole body protein and lipid content were affected by the dietary oil source. Fish oil diets increased long‐chain (LC) PUFAs content in the edible tissues, while vegetable oil‐based diets increased short‐chain (SC) PUFAs. Vegetable oil diet tended to decrease the fish protein content. A higher lipid liver content was observed in meagre fed the vegetable oil blend. The results also suggested the ability of meagre to convert SC‐PUFA to LC‐PUFA when the vegetable oil is included in their diet. The possibility for partial substitution of fish oil by vegetable oil in meagre diets, resulting in lower dependence of fish oil in meagre farming, is also demonstrated here. Practical applications: The growing importance of aquaculture for basic food supply, and the urge for cost‐effective and sustainable feeds that maintain or even increase fish quality, makes the search for alternatives to common feeds a route of upmost importance, as the vegetable oil here addressed. SC‐PUFA and LC‐PUFA contents of the studied tissues increased with diets supplemented with 17% oil level, which may ultimately add more value to this farmed species. These results indicate the possibility of the partial substitution of fish oil by vegetable oil in meagre diets, resulting in lower dependence on fish oil for fish farming. Meagre were fed with different dietary lipid sources and levels, with or without selenium supplementation, in a total of eight experimental diets during 60 days, in a 2 × 2 × 2 factorial design. Fish oil diet increases HUFAs and vegetable oil diet increases PUFAs in body composition. There is great potential for partial substitution of fish oil by vegetable oil in meagre ( Argyrosomus regius ) diets, resulting in lower dependence of fish oil in meagre farming. Abstract : Meagre were fed with different dietary lipid sources and levels, with or without selenium supplementation, in a total of eight experimental diets during 60 days, in a 2 × 2 × 2 factorial design. Fish oil diet increases HUFAs and vegetable oil diet increases PUFAs in body composition. There is great potential for partial substitution of fish oil by vegetable oil in meagre ( Argyrosomus regius ) diets, resulting in lower dependence of fish oil in meagre farming.